Efficiency evaluation of material and energy flows, a case study of Chinese cities. (20th January 2016) - Song, Tao; Yang, Zhenshan; Chahine, Teresa
Abstract: The environmental impact of materials and energy is an important concern when cities and regions produce goods and services. To examine this requires an evaluation tool which can deal with the complex system of resources, energy inputs, products and wastes involved. This paper evaluates the urban material and energy flow efficiencies of 31 cities in China using a combination of the Data Envelopment Analysis model and Principal Component Analysis method. The results show that the urban flow system is composed of several input and output principal components, including energy, materials, urban capital investment, overall output, wastes, and others. In 2010, 16 cities were efficient as judged by the material and energy inputs and outputs. The remaining 15 cities were not efficient, primarily due to product shortfalls and waste excesses. Since 2000, half of the analyzed cities experienced a decline in the urban flow efficiencies, while only six cities showed a positive trend. The reasons include excess inputs of coal, coke, electricity, cement, investment, as well as output shortfalls in terms of overall output, wastes, services, agriculture and transport. We conclude that key priorities for improving urban systems with material and energy flow inefficiency are the use of urban renewable supplies, focus on sustainable endogenous development model, and improvement management of waste output, in order to increase efficiency and sustain economic growth. Highlights: A method of combining DEA and PCA is presented to examine energy and material flows of cities. Urban material and energy flow efficiencies were analyzed for 31 Chinese cities. Since 2000, most of Chinese sample cities experienced a decline in the urban flow efficiencies. Reasons include excess energy inputs and output shortfalls of services and agriculture.